A semantic cloud infrastructure for dataintensive medical research. (2015) - Kaniovskyi, Yuriy; Benkner, Siegfried; Borckholder, Chris; Wood, Steven; Nowakowski, Piotr; Saglimbeni, Alfredo; Lobo, Tomas Pariente
The European virtual physiological human initiative develops a platform, called VPHShare, for understanding physiological processes in the human body in terms of anatomical structure and biophysical mechanisms. Besides storing, sharing, integrating and linking a wide variety of heterogeneous biomedical datasets relevant to the VPH community, the project envisions the facilitation of a secure data infrastructure, as well as search and exploration facilities based on semantic technologies. The data infrastructure and management platform are built on top of a hybrid cloud environment. The data management platform offers tools that cover the whole lifecycle of datasets including integration, selection, semantic annotation and publishing datasets as a service. A comprehensive user interface enables endusers to search and to explore biomedical data with support of semantic technologies, concealing the complexity of the underlying service environment. In this paper we describe the data infrastructure that has emerged in context of the project.